The Effects of Melatonin on the Descending Pain Inhibitory System and Neural Plasticity Markers in Breast Cancer Patients Receiving Chemotherapy: Randomized, Double-Blinded, Placebo-Controlled Trial - Palmer, Ana Claudia Souza; Souza, Andressa; dos Santos, Vinicius Souza; Cavalheiro, José Antônio Crespo; Schuh, Fernando; Zucatto, Angela Erguy; Biazus, Jorge Villanova; Torres, Iraci Lucena Da S.; Fregni, Felipe; Caumo, Wolnei (Frontiers in Pharmacology, 2019)
Background: Adjuvant breast cancer chemotherapy (ACBC) has been associated with fatigue, pain, depressive symptoms, and disturbed sleep. Accordingly, previous studies in non-cancer patients showed that the melatonin could improve the descending pain modulatory system (DPMS). We tested the hypothesis that melatonin use before and during the first cycle of ACBC is better than placebo to improve the DPMS function assessed by changes on the 0-10 Numerical Pain Scale (NPS) during the conditioned pain modulating (CPM-task) (primary outcome). The melatonin`s effects were evaluated in the following secondary endpoints: heat pain threshold (HPT), heat pain tolerance (HPTo) and the neuroplasticity state assessed by serum brain-derived neurotrophic factor (BDNF), Tropomyosin Kinase Receptor B (TrkB), and S100B-protein also, whether melatonin`s effects on pain and the neuroplasticity are due more so to its impact on sleep quality. Methods: Thirty-six women, age 18 to 75 years old, scheduled for their first cycle of ACBC were randomized to receive 20mg of oral melatonin (n=18) or placebo (n=18). The effect of treatment was assessed by changes delta [∆-values (prior minus treatment end)] in psychophysical pain measures, serum BDNF, TrkB, and S100B. Results: MANCOVA revealed that the changes in the NPS (0-10) during the CPM-task evaluated by ∆-means of each group, mean difference (md) between two groups with their respective confidence interval (CI, 95%) was (-1.07 vs. 2.76); md=–3.83, (-5.66 to -2.00)], respectively. The η²partial=0.60 indicates that the melatonin effect explains 60% of the variance in the CPM-task. The melatonin reduced the serum levels of neuroplasticity markers: BDNF [∆-means (-30.64 vs. 1.29); md=-32.93; (-50.19 to -13.67)]; TrKB [∆-means (-0.33 vs. 0.09), md=-0.43; (-0.66 to - 0.25)] and S00B-protein [∆-means (-14.85 vs. 2.22); md=-16.87; (-31.30 to -2.45)]. However, melatonin`s effect increased in the HPTo and HPT, and its effects on pain and the neuroplastic state are not due to its impact on sleep quality. Conclusions: These results suggest that oral melatonin, together with first ACBC, counteracts the dysfunction in the inhibitory DPMS and improves pain perception measures. Also, it shows that changes in the neuroplasticity state mediate the impact of melatonin on pain.